Chemotherapy-Induced Amenorrhea – An Update - Liedtke, C.; Kiesel, L. (Geburtshilfe und Frauenheilkunde, 2012)
Because of the heterogeneity in the definition of chemotherapy-induced amenorrhea (CIA) there are distinct differences in the literature with regard to its incidence as well as its dependence on various influencing factors. The occurrence of CIA varies greatly depending on the applied chemotherapy. The pathogenesis of CIA is especially based on a reduction of ovarian reserves. Various sonographic and biochemical factors can be used to exclude or confirm CIA. This is particularly important when an endocrine therapy with tamoxifen is not possible and the use of aromatase inhibitors is under consideration. CIA and especially the frequently thereby resulting early menopause can lead to pronounced restrictions in the quality of life of the affected patients, not least due to the resulting infertility. On the other hand, various studies have shown that CIA may have a positive prognostic significance. Thus, the identification of measures to prevent CIA (for example, through the use of GnRH analogues) is of particular importance.
Keywords: chemotherapy-induced amenorrhea; breast cancer; chemotherapy; GnRH analogues